Traditional ecological knowledge and utilization of rice in Sukoharjo District, Central Java, Indonesia - Kusuma, Lathifah Aninda; Damayanti, Kharisma; Damayanti, Julianatasya Tantri; Nisa, Jamilatun; Nurwulandari, Murni; Abu Nazar, Irfan; Yap, Chee Kong; Md. Naim, Darlina; Setyawan, Ahmad Dwi (Smujo International, 2023)
Kusuma LA, Damayanti K, Damayanti JT, Nisa J, Nurwulandari M, Nazar IA, Yap CK, Md. Naim D, Setyawan AD. 2023. Traditional ecological knowledge and utilization of rice in Sukoharjo District, Central Java, Indonesia. Intl J Bonorowo Wetlands 13: 78-85. Rice (Oryza sativa L.) is one of Indonesia's staple foods and a source of income for some communities. Sukoharjo District is one of Central Java's most promising rice producing areas. In managing rice farming, the community incorporates local knowledge and discovers collective understanding about rice plants. The research was conducted to determine the existence of Traditional Ecological Knowledge (TEK) by the Javanese people of Sukoharjo District, Central Java, Indonesia in managing rice varieties and influencing factors, as well as to learn about the community's perception of rice plants; the research employs a qualitative and quantitative ethnobiological approach. The results showed that although agriculture in Sukoharjo District is included in semi-modern agriculture, the community has TEK, which includes various rice varieties and paddy fields. Farmers in Sukoharjo District use Inpari 32 and in small quantities also the IR 64 rice varieties to manage their paddy fields instead of other varieties. Rice is widely used in various traditions, such as rasulan, bersih desa, kacar kucur (weddings), syukuran, and kenduren. Many parts of the rice plant are also used, such as rice stems (straw), grain, husks, bran, and rice. A small part of the Sukoharjo community uses rice as an important role in cultural behavior and in maintaining the rice varieties' biodiversity well. In managing agriculture, some communities still use traditional techniques and adjustments to modern technology, such as using modern tools and human labor to plant seeds. The application of rice in every activity of the people of Sukoharjo District shows a complex relationship between humans and nature.